Facile and Mild Displacement of Nitrite Ions in Electron-Deficient Nitroarenes by Alkyl or Aryl Thiols in the Presence of Magnesium Methoxide as a Solid Base Catalyst - Naeimi, Hossein; Moradian, Mohsen (Synlett, 2012)
The nucleophilic aromatic substitution reaction (SNAr) between nitroarenes (having electron-withdrawing groups in the ortho or para position), and alkyl- or arylthiols using magnesium methoxide as a solid base catalyst is described. This method leads to the creation of a series of valuable compounds from arylsulfides via nucleophilic displacement of the nitro group with the sulfanyl moiety. This facile method is a synthetically useful process, and it is significant that the nucleophile is promoted effectively by magnesium methoxide as a base in N,N-dimethylformamide. The displacement of then nitrite ion occurred in the presence of a variety of functional groups that caused an electron-deficient ring such as aldehyde, ketone, ester, cyano, and nitro groups.
Keywords: nitroarene; thiol; magnesium methoxide; aryl thioether